Modernization of the law enforcement system at the current stage of digital transformation - Kubaienko, Andrii V.; Okhrimenko, I.; Kryzhanovska, O. (Denmark : Faculty of Law Aalborg Academy of Sciences, 2022)
Political and economic disagreements of the last decade have caused the need to reform various institutions in the world, including the system of law enforcement agencies. From here, it follows that the problems of modern understanding of the law enforcement system and its reformation in the conditions of digitization and development of the information society gain relevance.

The aim of the article is to determine modern approaches to the modernization of the law enforcement system in the conditions of digital transformation and the need to approach European and world standards. Attention was paid to the interrelationship of digitalization processes with the level of effectiveness of law enforcement activities. The need for changes in the law enforcement system with mandatory consideration of the following positions was also substantiated: a) society’s expectations in the sphere of ensuring law and order as well as legality; b) national traditions and peculiarities, including those related to the construction of the law enforcement system; c) positive experience of states in terms of law enforcement and observance of human rights and freedoms; d) the need to set real tasks before law enforcement agencies that correspond to their potential capabilities.
Kubaienko A., Okhrimenko I., Kryzhanovska O. Modernization of the law enforcement system at the current stage of digital transformation. Journal of law and political sciences. 2022. Vol (35). P.384-400.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; modernization; law enforcement system; law enforcement agencies; digitalization; law enforcement activities